Congenital candidiasis – a diagnostic challenge - Rolim, Sara (2021)
Introduction: Congenital candidiasis is a rare intrauterine infection characterized by vesicular and pustular skin lesions appearing in the first six days of life. Clinical case: The authors describe the case of a full-term infant presenting erythematous macules, vesicles and pustules involving the trunk and extremities and cervical burn-like dermatitis at birth. Mycological skin lesion culture was positive for Candida albicans. Blood culture was positive for methicillin-sensitive Staphylococcus aureus. After systemic antifungal and antibiotic therapy was started, the newborn remained asymptomatic with lesion improvement. Discussion/ Conclusion: Herein is reported a case of congenital candidiasis in a full-term infant, with a successful recovery. The rarity of congenital candidiasis can lead to delayed diagnosis and unnecessary treatment. This case shows that fungal infection should be considered in the differential diagnosis of vesiculopustular skin lesions in neonates. Systemic therapy should be initiated if invasive candidiasis is suspected.